Enhancing Quality of Life for Caregivers of Adolescents with Emotional Disorders through Digital Skills - Kalogeratos, Gerasimos; Anastasopoulou, Eleni; Tseremegklis, Chrysostomos; Avramidi, Eleni (Technium Education and Humanities, 2024)
Background: Caring for adolescents with emotional disorders places a substantial burden on caregivers, negatively influencing their quality of life and well-being. An increase in digital skills may provide caregivers with additional resources to support their charges and enhance their own mental health. Objective: This paper seeks to investigate the impact of interventions that improve digital skills for caregivers, targeting the enhancement of their ability to support adolescents with emotional disorders, with the goal of augmenting both their and the adolescents’ quality of life. Methods: The paper synthesizes research findings on the efficacy of digital interventions, such as psychoeducation and skills training, and examines the importance of digital skills in managing the emotional and social challenges often encountered by caregivers. It also discusses the role of informal caregivers and the burden they experience across different cultures and socioeconomic contexts. Results: Effective strategies for reducing caregiver distress include interventions to bolster emotional and social skills, leadership capabilities, and coping mechanisms. Classification systems for mental disorders and the need for long-term care plans are also reviewed to provide a comprehensive understanding of the context in which caregivers operate. Conclusion: The study suggests that a comprehensive support approach—including psychoeducation, skills training, and therapeutic counseling—is necessary for enhancing caregivers’ well-being. These interventions are crucial for aiding caregivers in managing their mental health needs and improving the overall outcomes for adolescents with emotional disorders.